Solderability, microstructure, and thermal characteristics of Sn‐0.7Cu alloy processed by high‐ energy ball milling - Sharma, Ashutosh; Oh, Min Chul; Chae, Myoung Jin; Seo, Hyungtak; Ahn, Byungmin (Metals, 2020)
In this work, we have investigated the role of high‐energy ball milling (HEBM) on the evolution of microstructure, thermal, and wetting properties of an Sn‐0.7Cu alloy. We ball‐milled the constituent Sn and Cu powders in eutectic composition for 45 h. The microstructural studies were carried out using optical and scanning electron microscopy. The melting behavior of the powder was examined using differential scanning calorimetry (DSC). We observed a considerable depression in the melting point of the Sn‐0.7Cu alloy (≈7 °C) as compared to standard cast Sn‐0.7Cu alloys. The resultant crystallite size and lattice strain of the ball‐milled Sn‐0.7Cu alloy were 76 nm and 1.87%, respectively. The solderability of the Sn‐0.7Cu alloy was also improved with the milling time, due to the basic processes occurring during the HEBM.
Keywords: High‐energy ball milling; Interface; Joining; Microstructure; Soldering